2005
DOI: 10.2174/1568005054201599
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated- or Killed-Virus HIV/AIDS Vaccines

Abstract: Inactivated or "killed" virus (KV) is a "classical" approach that has produced safe and effective human and veterinary vaccines but has received relatively little attention in the effort to develop an HIV/AIDS vaccine. Initially, KV and rgp120 subunit vaccines were the two most obvious approaches but, unfortunately, rgp120 has not been efficacious and the KV approach has been limited by a variety of scientific, technical, and sociological factors. For example, when responses to cellular antigens, present on SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 119 publications
0
16
0
1
Order By: Relevance
“…Safety concerns prohibit the use of live-attenuated virus as immunogen. 199 Many different approaches with recombinant technologies have been pursued over the past two decades. Initially, efforts were focused on generating neutralising antibodies with recombinant monomeric envelope gp120 (AIDSVAX) as immunogen.…”
Section: Sexual Transmissionmentioning
confidence: 99%
“…Safety concerns prohibit the use of live-attenuated virus as immunogen. 199 Many different approaches with recombinant technologies have been pursued over the past two decades. Initially, efforts were focused on generating neutralising antibodies with recombinant monomeric envelope gp120 (AIDSVAX) as immunogen.…”
Section: Sexual Transmissionmentioning
confidence: 99%
“…24 An advantage of this approach is that the viral antigens are presented in a "native" conformation and composition, thereby presenting a natural immunogenic profile. However, this approach is currently not favored with HIV because of a number of overriding concerns, such as the potential presence of residual infectious virions due to incomplete inactivation, the likelihood that the harsh microbicidal agents will alter the native conformation of the virus, and the requirement for extensive and composition-altering purification steps to remove the toxic microbicide.…”
Section: Figmentioning
confidence: 99%
“…Nevertheless, efforts continue to be made to find agents that are capable of completely inactivating whole viruses, but are at the same time mild enough not to appreciably disturb the native conformation of the viral envelope. [24][25][26][27][28] The highly effective HIV-killing properties of T-NCl, the nontoxic properties of this natural compound, and its selectivity for viral cysteines all suggested that this agent may prove successful in the preparation of effective and safe whole-killed HIV vaccines. The present study therefore examined this possibility in vivo with the murine AIDS (MAIDS) model.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations